1991
DOI: 10.3109/02656739109004973
|View full text |Cite
|
Sign up to set email alerts
|

Combination radiotherapy of urinary bladder carcinoma with chemohyperthermia

Abstract: The combination therapy of urinary bladder cancer with radiation and hyperthermia with bleomycin was investigated. Immediately following daily external irradiation (40 Gy/4 weeks), patients were irrigated with a solution of warmed saline (intravesical temperature, 42-43 degrees C) containing 30 micrograms/ml bleomycin. Of a total of 56 patients, complete responses were observed in 25, and partial responses in 21. Among T2-T3 cases, an 84% response rate was noted in combination therapy, whereas a 56% response r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…HT was delivered by intravesical infusion of warmed saline solution containing bleomycin. The RTHT group had a higher response rates (RTHT: 84%, RT: 56%, p  < 0.001) with decreased toxicity rates (less bladder capacity reduction) (99). In a different approach, 49 patients with nodal-negative disease of all T stages were treated with a hypofractionated RT scheme (24 Gy, 4 Gy/fraction) with or without HT.…”
Section: Clinical Evidence Of Combined Thermoradiotherapymentioning
confidence: 99%
“…HT was delivered by intravesical infusion of warmed saline solution containing bleomycin. The RTHT group had a higher response rates (RTHT: 84%, RT: 56%, p  < 0.001) with decreased toxicity rates (less bladder capacity reduction) (99). In a different approach, 49 patients with nodal-negative disease of all T stages were treated with a hypofractionated RT scheme (24 Gy, 4 Gy/fraction) with or without HT.…”
Section: Clinical Evidence Of Combined Thermoradiotherapymentioning
confidence: 99%
“…The RT dose was 40 Gy delivered at 4 Gy/fraction, twice weekly with Adriamycin, 5-fluorouracil and cisplatin chemotherapy. Matsui et al [19] reported a triple modality treatment in all stages of bladder cancers using RT (40 Gy/4 weeks) and daily hyperthermic irrigation of the bladder with bleomycin following RT. Of the 56 patients, 25 achieved CR.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be effective for non-muscle-invasive bladder cancers when applied intravesically with instillation of CT agents, such as, mitomycin C [14,15]. In MIBC, HT has been used with radiotherapy (RT) alone either as a preoperative or definitive treatment [16,17], or with CTRT, both resulting in positive outcomes [18][19][20]. Thermal radiosensitisation has been primarily attributed to reoxygenation, selective killing of radioresistant hypoxic tumour cells, and inhibition of repair of radiation-induced DNA damage [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several Japanese institutions have published their experiences with thermoradiotherapy in bladder cancer from the late 1970s through the early 1990s. Matsui et al described a Yokohama City University series in 1991 [55]. Fifty-six patients were included in this report.…”
Section: Hyperthermia and Radiation In Bladder Cancermentioning
confidence: 99%